Changes in Maternal Body Mass Index, Weight Gain and Outcome of Singleton Pregnancies from 2000 to 2015 - Noever, Kathrin; Schubert, Julia; Reuschel, Edith; Timmesfeld, Nina; Arabin, Birgit (Geburtshilfe und Frauenheilkunde, 2020)
Introduction Maternal obesity and excessive gestational weight gain (GWG) affect the outcomes of women and their offspring. Our aim was to evaluate population-based data from Germany.Material and Methods Data from 583 633/791 514 mother-child pairs obtained from the perinatal database in Hesse for the period from 2000 to 2015 were used after excluding incomplete or non-plausible datasets. Early-stage pregnancy maternal body mass index (BMI) and GWG were evaluated. Significant outcome changes were calculated using linear or logistic regression models.Results The mean maternal age increased from 29.9 to 31.28 years; GWG increased from 445.1 to 457.2 g/week (p < 0.01). Similarly, rates for both overweight and obesity rose from 31.5 to 37.5% (p < 0.001). Cesarean section rates rose from 22.8 to 33.2% (p < 0.001) and rates of postpartum hemorrhage increased from 0.6 to 1% (p < 0.001). There was no significant change in the rates for stillbirth or perinatal mortality (p = 0.92 and p = 0.53 respectively), but there was an increase in the rates of admissions to neonatal intensive care units from 7.8 to 9.5% (p < 0.0001). The percentage of newborns with an Apgar score of < 7 at 5 minutes increased from 1 to 1.1% (p < 0.01) and the rate of neonates with an umbilical artery pH of < 7.1 rose from 1.7 to 2.4% (p < 0.01).Conclusions In just 15 years, pre-pregnancy BMI and GWG rates of women with singleton pregnancies have increased, and this increase has been accompanied by a significant rise in the rate of cesarean sections and a significant worsening of short-term maternal and neonatal outcomes. It is time to discuss the risks and the short-term and more worrying long-term consequences for mothers and their offspring and the future impact on our healthcare system.
Keywords: body mass index (BMI); gestational weight gain; overweight; obesity